MARKETING ACTIVITIES IN CULTURAL INSTITUTIONS (International conference on multidisciplinary science, 2023)
this article presents concepts for the development of marketing strikes of the cultural sphere. The specifics of marketing concepts in organizations of the art and cultural sphere are highlighted. The main focus is on the processes of forming a marketing portfolio based on the requirements and desires of customers.